Family Types and Intimate Partner Violence: A Historical Perspective - Tur-Prats, Ana (The Review of Economics and Statistics, 2019)
This paper examines the long-term determinants of intimate partner violence (IPV) by analyzing its relationship with traditional family structures: stem families in which one child stays in the parental household and nuclear families in which all children leave the household upon marriage. My hypothesis is that coresidence with a mother-in-law increases a wife's contribution to nondomestic work, which may decrease the level of violence. I find that areas where stem families were socially predominant in the past currently have a lower IPV rate, and use differences in inheritance laws in medieval times as an instrument for the different family types.